Effect of External Audit Opinions and Audit Committees on Financial Resource Management in Public Sector Entities - Frank Mwombeki (Ilomata International Journal of Tax and Accounting, 2023)
External audit opinions (EAO) and Audit committees (AC) have been studied in different contexts, yet the link between them and the management of financial resources, especially in government entities in Tanzania, has empirically not been captured. This paper examined the influence of EAO and AC on managing financial resources taking Tanzania government entities as a reference. It uses resources dependency theory to explain the main topic. Data were collected on 230 government entities from Controller and Auditor General (CAG) reports and audited financial statements for 2014/15 to 2019/20. Descriptive statistics and the Fixed effect technique were used to analyze data. The results show that unqualified audit opinion occurred most among public entities. Specifically, the qualified audit opinion occurred most in LGAs. Also, a significant frequency of AC weaknesses appeared in LGAs and Public BICA.Moreover, the estimation results show that audit report positively and significantly influences financial resource management (FRM), whereas AC weakness has a negative relationship with FRM. Therefore, the President’s office and the Parliament should emphasize the management of resources strategies in public entities, especially LGAs. This paper will add knowledge on EAO and AC as tools for financial resources management in government entities.